Recursos genéticos em quintais e comercialização de plantas de uso medicinal no município de São Miguel-RN - Freitas, Ana Valeria Lacerda (2009)
This works aimed at the carrying out an ethnobotanical study on plant genetic resources in the Sao Miguel city, Rio Grande do Norte, Brazil. The work was divided into three chapters, which dealt the first a general introduction and a review of literature review. In second chapter the study covered of the use of medicinal plants in the family groups agriculture communities on the Sitio Cruz, emphasizing are medicinal plants and considering the views of children on these environments. The third chapter, proposes included a study with raizeiros the study on Sao Miguel city on aspect of marketing of medicinal plants. The methodology used in the last two chapters covering qualitative and quantitative, and conducted semi-structured interviews and other data collection techniques. All the families around the Sitio Cruz have a singular importance, and consist of several areas with different functions and meanings. These areas are composed of variety of ethnospecies, as demonstrated by the informants, a broad understanding of these plants and their uses. As the marketing of medicinal plants and products, it was found that the raizeiros of Sao Miguel-RN are people aged between 34 and 81 years engaged in the activity is an average of 14 years, earning a monthly income lower than a minimum wage. The plants and products are in demand for various types of diseases, and the dried plants and products benefit from the main forms of marketing.